Pengaruh Corporate Governance Terhadap Laporan Keuangan Pada Sektor Transportasi - Winny Alwijaya; Rolendo Rolendo; Tetty Tiurma Uli (Center for Research and Community Service (LPPM) University of Abulyatama, 2019)
The integrity of financial statements in the transportation company sector is much below the standard requirements of the IDX and many transportation sectors are not listed on the IDX. Financial report integrity (dependent variables) are analyzed by independent variables consisting of x1 = Board of Directors size, x2 = Proportion of Independent Commissioners (PKI), x3 = Audit Committee (KA) and x4 = Institutional Ownership (KI). The value of the F test regression results is 2.475 with a significance of 0.05, while the t test is only institutional ownership that has an effect of 3.035 and significant 0.03 means that the greater the number of institutional ownership, the better the integration of financial statements.